Barriers to emergency department usage during the COVID‐19 pandemic. Issue 6 (12th November 2020) - Niforatos, Joshua D.; Chaitoff, Alexander; Zheutlin, Alexander R.; Feinstein, Max M; Raja, Ali S.
Abstract: Objective: The objective of this study was to determine the public's likelihood of being willing to use an emergency department (ED) for urgent/emergent illness during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: An institutional review board–approved, cross‐sectional survey of a non‐probability sample from Amazon Mechanical Turk was administered May 24–25, 2020. Change in self‐reported willingness to use an ED before and during the pandemic (primary outcome) was assessed via McNemar's test; COVID‐19 knowledge and perceptions were secondary outcomes. Results: There were 855 survey participants (466 [54.5%] male; 699 [81.8%] White; median age 39). Proportion reporting likelihood to use the ED pre‐pandemic (71% [604/855]) decreased significantly during the pandemic (49% [417/855]; P  < 0.001); those unlikely to visit the ED increased significantly during the pandemic (41% [347/855] vs 22% [417/855], P  < 0.001). Participants were unlikely to use the ED during the pandemic if they were unlikely to use it pre‐pandemic (adjusted odds ratio, 4.55; 95% confidence interval, 3.09–6.7) or correctly answered more COVID‐19 knowledge questions (adjusted odds ratio, 1.37; 95% confidence interval, 1.17–1.60). Furthermore, 23.4% (n = 200) of respondents believed the pandemic was not a serious threat to society. Respondents with higher COVID‐19 knowledge scores were more likely to view the pandemic as serious (odds ratio, 1.57; 95% confidence interval, 1.36–1.82). Conclusions: This survey study investigated the public's willingness to use the ED during the COVID‐19 pandemic. Only 49% of survey respondents were willing to visit the ED during a pandemic if they felt ill compared with 71% before the pandemic.